New voices in Greek Orthodox thought : untying the bond between nation and religion - Willert, Trine Stauning (Ashgate new critical thinking in religion, theology, and biblical studies., 2014)
Demonstrating that in late modernity, parallel to rising nationalisms, there is a shift towards religious communities becoming the central axis for cultural organization and progressive thinking, this book presents Greece as a case study based on empirical field data from contemporary theology and religious education, and makes a unique contribution to ongoing debates about the public role of religion in contemporary Europe.